PERENCANAAN PENANGANAN PERGERAKAN TANAH DENGAN METODE SOLDIER PILE DI STA. 07+100 JALUR PIPA PENYALUR KM. 53 – SKG BONTANG - BUDIMAN, LALU ELHAM (KURVA S JURNAL MAHASISWA, 2018)
Gas Pipeline Right of Ways KM. 53 - Bontang SKG (Gas Compressor Station) owned by PT. Pertamina Gas (Pertagas) has a potential landslide. There are 3 gas pipelines in the line, which are 2 carbon steel pipes with a diameter of 16 "and 1 carbon steel pipe with a diameter of 20". The gas pipeline is embedded in the soil with a depth of at least 100 cm from the ground. This causes gas pipelines to be vulnerable to risks caused by land movements. On February 7, 2017 found fault in this area. To prevent the spread of land movement areas, it is feared to affect the integrity of the nearest pipeline. Therefore, fast and precise handling is needed to overcome the movement of the land. The method used to collect soil data using the Cone Penetration Test. While the slope analysis method using the Slope / W Geo Studio 2018 R2 program with the analysis method used is the Bishop slice method. From the results of the analysis and calculation, it can be concluded that the handling of the movement of land at Sta. 07,100 Gas Line Pipes Km. 53 - SKG Bontang can be used Soldier Pile with specifications: Length of Pile Soldier 12 Meters, Diameter 50 cm, Main reinforcement 8D26, Shear reinforcement D12 - 145 mm and concrete quality K - 250 (20.75 Mpa). This Soldier Pile is effective as a method of slope reinforcement because it has cut the maximum landslide area of 6.193 meters.